Sistem Informasi Akuntansi Pembelian dan Pengeluaran Kas Sebagai Pengendalian Intern pada PT XYZ - Iswandir Iswandir (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2016)
The purpose of this research is to determine the suitability of the information system purchases and cash expenditures applied to the PT. XYZ theory Information Systems Generally Accepted Accounting. The company uses a computer accounting program Accurate 4, generally recording purchases, starting from the purchase request to the internal control, in accordance with accounting principles, but there are still some conditions that need to be considered, namely, there are two jobs done by one person, and suggested better companies utilize passwords basis of the work is not based on accurate system module 4